Analisis Vegetasi Di Area Kebun Kakao Milik Masyarakat Lokal Papua Distrik Sidey Manokwari, Papua Barat - Slamet Arif Susanto (Jurnal Pro-Life, 2022)
Cocoa (Theobroma cacao L.) cultivation by local communities in Papua Indonesia is still done traditionally using shade plants which generally grow naturally. The purpose of this study was to identify trees that grow naturally in three cocoa plantation areas of the local tribe, Sidey District Manokwari, West Papua. This research is an exploratory study using vegetation analysis techniques. Vegetation data collection was carried out using a 20 m × 20 m nested square plot method. The results showed that there were variations in the composition of vegetation and environmental parameters in the three research locations. Overall 70% is dominated by seedlings and saplings while only 30% of mature trees. The Womnowi Village (KW) location was dominated by Dracontomelon dao, Homalium foetidum and Octomeles sumatrana trees, while at the Kaironi Village (KK) and Sidey Makmur Village (SM) locations it was dominated by Durio zibethinus, Piper aduncum and Naphelium lappaceum. The index of diversity and evenness in the seedlings and saplings group was categorized as moderate, while in the mature tree group it was classified as low. Cocoa shade trees in the KW location have species similar to natural forests and need further investigation in terms of ecological and conservation functions.